Pengaruh Konseling Analisis Transaksional Dalam Mengentaskan Masalah Siswa Yang Terisolir Karena Egois - Wathoni, Muhammad Zainul; Aulia, Fitri (Educatio, 2017)
AbstractThis study aims to determine the effect of transactional analysis counseling in alleviating problems of students who are isolated due to selfishness in class XI MA Nurul Iman Montong Good school year 2017/2018. This type of research is an experiment with Single Subject Design. The subject of this research was a class XI student. Data collection techniques using student questionnaires isolated because selfish and analyzed by using quantitative data in the form of numbers processed using simple statistics and qualitative data described and processed using narrative analysis. The results showed that the initial condition data of students before being given individual counseling was obtained using isolated questionnaires because they were selfish with a total score of 55 which was included in the isolated category, because they were in the range of 50 to <65. Individuals obtained a total score of 42 which was included in the slightly isolated category, because it was in the range of 35 s / d <50. This shows that the Transactional Analysis technique is effective for dealing with the problem of students who are isolated because of selfishness.